2014
DOI: 10.1097/mop.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent health literacy and the Internet

Abstract: More research is needed in this field to better understand the challenges and to propose effective solutions. However, a multifaceted approach that engages policymakers, educators, healthcare providers, online health information providers, and parents may be positioned to make the largest impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Despite the differing performance of each health literacy instrument, we found that at least one-third of adolescents did not have adequate health literacy skills, which in turn predicted their health outcomes. Compared to previous generations, adolescents nowadays face significant health challenges in the 21st century such as the shift in disease burden from traditional communicable diseases to non-communicable diseases and conditions [54] and challenges that adolescents face when using the Internet to access online health information [55]. Therefore, it is imperative to equip themselves with health literacy, particularly critical thinking and decision-making skills, to address these health challenges at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differing performance of each health literacy instrument, we found that at least one-third of adolescents did not have adequate health literacy skills, which in turn predicted their health outcomes. Compared to previous generations, adolescents nowadays face significant health challenges in the 21st century such as the shift in disease burden from traditional communicable diseases to non-communicable diseases and conditions [54] and challenges that adolescents face when using the Internet to access online health information [55]. Therefore, it is imperative to equip themselves with health literacy, particularly critical thinking and decision-making skills, to address these health challenges at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…For a majority of youth, online social networking sites are their first point of call when they want to find information, including health-related matters [17,18]. Thus, social media is a rich environment to recruit youth participants to participate in research.…”
Section: Use Of Social Media For Youthmentioning
confidence: 99%
“…Furthermore, traversing fragmented health services can be more difficult when transiting from child to adult services. [8][9][10][11][12] Youth healthcare can be a challenging area to work, partly because of limited support. [13][14][15][16] A systematic review suggested youth access to sexual and reproductive health services is hindered by service accessibility; privacy and confidentiality; and staff characteristics and competencies.…”
Section: Youth Healthmentioning
confidence: 99%
“…Although many are digitally literate, many have limited health literacy, partly because of stigma. Furthermore, traversing fragmented health services can be more difficult when transiting from child to adult services …”
Section: Introductionmentioning
confidence: 99%